Assessment of smallholder agrarian systems and the adoption of veterinary services and government schemes in Mirzapur, Uttar Pradesh - Utkarsh Kumar Tripathi; Anuradha Kumari; Manish Kumar; Vipin Maurya (Annals of Agricultural Research, 2026)
Livestock sustains rural livelihoods in Vindhyan region’s Mirzapur District, UP, where dairy dominates over secondary goats, sheep, and poultry, whose contributions to income, nutrition, and risk mitigation remain underexplored despite South Asian smallholder patterns. This survey of 576 households assesses their structure, management, inputs, and veterinary/government service adoption via structured data on ownership, breeds, production, feeding, and breeding, analyzed descriptively. In the study Vindhyan region’s Mirzapur District reveal dairy as the primary livestock pillar (52% priority), with goats (20% owners, mostly 1-2 indigenous animals for meat/milk at low yields of 0.5-2L/day sold Rs.40-60/L), sheep (>92% none, small flocks for meat/wool Rs.50-200/kg), and poultry (>90% none, backyard desi birds with sporadic eggs/meat) as marginal, subsistence assets amid high data gaps. Management relies on low-input feeds (berseem 30%, straws 36%, grazing 8.5%), mixed breeding (AI 31%, natural 23%), but veterinary use splits (29% formal, 46% informal/self), and government schemes remain low (<5% for insurance/credit/Kamdhenu yojna). These patterns emphasize needs for breed/feed/health upgrades and outreach to elevate small ruminants/poultry productivity and resilience. Based on these findings, improved smallholder livestock management—through breed enhancement, better feeding/health practices, and expanded veterinary/insurance access—can boost productivity, nutrition, and resilience, playing a crucial role in achieving sustainable development goals in Vindhyan region’s rural livelihoods.